Maternal and child health in Bangladesh: a critical look at the policy and the sustainable development goals - Khan, Nur Newaz (Asian Journal of Medical and Biological Research, 2017)
Based on secondary analysis, this paper places a critical discussion looking back in history of maternal health achievements by Bangladesh, future adaptability and potentials forwarding to the sustainable development goals (SDGs) set by United Nations. Since the transition from MDGs to SDGs, Bangladesh achieved a many progress in maternal health development but still grappling with many structural and cultural barriers. Implementation of policy documents in community level, lack of better infrastructure, health bureaucracy induced delays, culture of absenteeism among practitioners and lack good health governance are some major challenges still hindering a fostered progress in achieving the expected improvement in maternal and child health condition in community and broader level. Evidences discussed in this paper suggests that, the clauses related to implementation and maintenance need to be stronger in the maternal health policy for future direction and sustainable progress in maternal health. The policy should act in practice, not as a document, to improve maternal health and reducing mortality that would finally speed up the progress in achieving SDGs target in more pragmatic sense. Asian J. Med. Biol. Res. September 2017, 3(3): 298-304